Psychosexual education and training for adolescents with autism spectrum disorder: a systematic review - Duarte, Luísa (2022)
Introduction: Adolescents with autism spectrum disorder (ASD) may have limited access to reliable information on puberty and sexuality, and the core symptoms of ASD can lead to problems in romantic and sexual functioning, like engaging in less appropriate sexual behavior. Therefore, these adolescents may benefit from specialized psychosexual training programs. Objectives: To review the existing literature about psychosexual education and psychosexual training for adolescents with ASD. Methods: Systematic literature review. Results and Discussion: Sexual education programs targeting adolescents with ASD are scarce. The only adolescent-centered psychosexual training program that can currently be found in the literature is the Tackling Teenage Training (TTT) program, in which adolescents with ASD receive psychoeducation and practice communicative skills regarding topics related to puberty, sexuality, and intimate relationships. Statistically significant improvements in psychosexual knowledge, interpersonal boundaries, and social functioning are often described with the TTT program. On the other hand, the impact of the program on decreasing aggressive or problematic sexual behavior, decreasing worries about the future, and transferring the acquired knowledge to everyday life is more inconsistently reported. Conclusion: TTT seems to be an effective psychosexual educational program for adolescents with ASD, but further research on the translation of acquired knowledge into practice, improvement of romantic relational skills, and prevention of problematic sexual behavior and victimization is required. Since adolescents with ASD have the right to date, greater investment should be placed in sexual education programs specifically addressing the needs of this population.